Development of Materials Guide Increasing Taekwondo Level of Sragen Regency in 2018 - Handayani, Dwi; Soegiyanto, Soegiyanto; Rustiadi, Tri (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
Sragen regency has an active member of Taekwondo 1179 jeja according to February 2018 increase test. Referring to SOP PBTI regency/city administration should have basic guidance for training to enable them to take exams from geup 1 to DAN test. So the researcher is interested to conduct research to develop the manual which contains the training materials which refer to the district level improvement test referring to the provincial increase test. The objectives of this study resulted in training guidance of Taekwondo level increase in Sragen Regency and resulted in effective guidance for trainers and jeja. The research design used in this research is development or R & D. Development steps are potential and problem analysis, data and information collection, product design, product validation, product revision, product trial, and product revision. The feasibility test is performed by a Taekwondo material expert validator and a media and language expert validator. Small-scale book trials use 10 jeja and 40 jeja for large-scale trials. Types of data are quantitative and qualitative. Quantitative data were analyzed by descriptive percentage, while the qualitative data were analyzed by drawing conclusions. The data were collected by questionnaire instrument. The average percentage gained from the examination of two material expert validators is 88.6% which means the book is good to use. The results of the assessment of two validators of media and language experts, manuals are well-stated average percentage of 87.5%. Based on the criticism and suggestions from the validator, the book needs to be revised. After the revision phase, the module is tested. The results of small-scale trials are 87%, indicating that the book is declared good for use, whereas large-scale trials are 87.2% declared good and usable. Suggestions for product development is for jeja and coach to study the manual.